ORF3c is expressed in SARS-CoV-2-infected cells and inhibits innate sensing by targeting MAVS - Müller, Martin; Herrmann, Alexandra; Fujita, Shigeru; Uriu, Keiya; Kruth, Carolin; Strange, Adam; Kolberg, Jan E.; Schneider, Markus; Ito, Jumpei; Müller, Marcel A.; Drosten, Christian; Enßer, Armin; et al. (EMBO Reports, 2023)
Most SARS-CoV-2 proteins are translated from subgenomic RNAs (sgRNAs). While the majority of these sgRNAs are monocistronic, some viral mRNAs encode more than one protein. One example is the ORF3a sgRNA that also encodes ORF3c, an enigmatic 41-amino-acid peptide. Here, we show that ORF3c is expressed in SARS-CoV-2-infected cells and suppresses RIG-I- and MDA5-mediated IFN-β induction. ORF3c interacts with the signaling adaptor MAVS, induces its C-terminal cleavage, and inhibits the interaction of RIG-I with MAVS. The immunosuppressive activity of ORF3c is conserved among members of the subgenus sarbecovirus, including SARS-CoV and coronaviruses isolated from bats. Notably, however, the SARS-CoV-2 delta and kappa variants harbor premature stop codons in ORF3c, demonstrating that this reading frame is not essential for efficient viral replication in vivo and is likely compensated by other viral proteins. In agreement with this, disruption of ORF3c does not significantly affect SARS-CoV-2 replication in CaCo-2, CaLu-3, or Rhinolophus alcyone cells. In summary, we here identify ORF3c as an immune evasion factor of SARS-CoV-2 that suppresses innate sensing in infected cells.
CRIS-Team Scopus Importer:2023-11-03
Keywords: cryptic open reading frames; IFN antagonist; immune evasion; ORF3c; SARS-CoV-2